DINAMIKA SOSIAL PENGUASAAN LAHAN DI DESA BISSOLORO (STUDI KASUS DATARAN SEDANG KABUPATEN GOWA) - Mappa, Nurdin; Molla, Saleh (Jurnal Analisa Sosiologi, 2023)
Land control for farmers is very important, without land farming cannot be carried out, however, this condition is increasingly worrying because of the large amount of land being converted into non-agricultural land. Every year the land converted into non-agricultural land reaches 110,000 hectares per year (Ayun et al., 2020). This condition is getting more and more uncontrollable so that it is very worrying about the sustainability of agriculture as well as threatening national food security at the same time it can affect human life itself because food is a primary human need, therefore research is very important to carry out as academic study material to be able to make all parties aware. This research aims to analyze the social dynamics of farmers' agricultural land control in the temperate plains in Bissoloro Village, Bongaya District, Gowa Regency. The data collection technique is through interviews using question sheets, while the data analysis technique is a qualitative analysis using a case study approach. The analysis steps are carrying out data verification, data display, and conclusion. The results of the analysis show that there are social dynamics of land tenure in Bissoloro Village, where the average area of land controlled by farmers is 1.1 Ha with land tenure status in the form of ownership of 80.5% and land rental of 18.5%. Land ownership was obtained from inheritance 76.2% or 15.9 Ha and through purchase 9.52% or 1.6 Ha. When compared with the national average land tenure of 0.5 Ha, farmers' control of agricultural land in Bisssoloro is still wider so it can still be sustainable.Keywords:  Farmers, Land,  Mastery, Medium, Plains AbstrakPenguasaan lahan bagi petani sangat penting, tanpa lahan usahatani tidak dapat dijalankan, akan tetapi kondisi ini semakin memprihatinkan oleh karena banyaknya lahan yang dikonversi menjadi lahan non pertanian. Setiap tahun lahan yang terkonversi menjadi lahan non pertanian mencapai 110.000 hektar pertahun (Ayun et al., 2020).  Kondisi ini  semakin lama semakin tak terkendali sehingga sangat mengkhawatirkan akan keberlanjutan pertanian sekaligus mengancam ketahanan pangan secara nasional dan sekaligus dapat mempengaruhi kehidupan manusia sendiri oleh karena pangan merupakan kebutuhan primer manusia, oleh karena itu penelitian sangat penting dilakukan sebagai bahan kajian akademik untuk dapat menyadarkan semua pihak. Tujuan penelitian ini adalah menganalisis dinamika sosial  penguasaan lahan pertanian petani pada dataran sedang di Desa Bissoloro Kecamatan  Bongaya Kabupaten Gowa.  Teknik pengumpulan data melalui wawancara dengan menggunakan lembar pertayaan,  sedangkan tehniks analisis data dengan analisis kualitatif dengan pendekatan studi kasus. Adapun langkah analisis yaitu melakukan previkasi data, displai data,  dan penarikan kesimpulan. Hasil analisis menunjukkan  bahwa ada dinamika sosial  penguasaan lahan di Desa Bissoloro,  dimana rata-rata luas lahan  yang dikuasai perpetani adalah 1,1 Ha  dengan status penguasaan lahan berupa kepemilikan 80,5% dan sewa lahan 18,5%.  Kepemilikan lahan diperoleh dari warisan 76,2% atau 15,9 Ha, dan melalui pembelian  9,52%  atau 1,6 Ha.  Jika dibandingkan dengan rata-rata   penguasaan lahan   nasional  yaitu 0,5 Ha maka penguasaan petani terhadap lahan pertanian di Bisssoloro masih lebih luas sehingga masih dapat  berkelanjutan.Kata kunci: dinamika,  penguasaan, lahan, petani, sosial